Organización contable en la ferretería de la señora Faican Paccha Paulina Elizabeth de la ciudad de Loja, periodo del 01 de abril al 30 de julio del 2023 - Delgado Balvuca, Fernanda Micaela (2024)
The present degree work titled "ACCOUNTING ORGANIZATION IN MRS. FAICAN PACCHA PAULINA ELIZABETH'S HARDWARE STORE ON THE CITY OF LOJA, PERIOD FROM APRIL 1ST TO JULY 30TH, 2023," was developed with the aim of providing the owner with clear and timely information for effective decision-making, as well as fulfilling a requirement to obtain a Bachelor's degree in Accounting and Auditing. To achieve the stated objectives, an inventory of the establishment's assets was conducted, which facilitated the design of the account plan and manual tailored to the commercial establishment's needs. This involved describing each account category, including Assets, Liabilities, Equity, Costs, Expenses, and Income. Subsequently, the initial inventory was established by physically verifying all products, goods, rights, and obligations held by the commercial establishment. This process resulted in a total asset valuation of $425,494.24, total liabilities of $32,987.11, and equity of $392,507.12, forming the Initial Situation Statement. The movement of the Merchandise account was managed by implementing the Multiple Account System, enabling the acquisition of detailed information for controlling the merchandise account. The accounting process then proceeded, involving data compilation and facilitating recording in auxiliary books. These records were subsequently presented in the daily ledger. After obtaining balances from the general ledger, the trial balance was prepared. Based on these balances, a worksheet was developed, including necessary adjustments and regulatory entries. This process led to the generation of financial statements. The Income Statement indicated a total income of $56.660,19 and expenses of $9281,45, resulting in a profit of $14,218.54 for the period from April 1st to July 30th, 2023. The Statement of Financial Position showcased assets totaling $434.566,21, liabilities of $26,195.45, and equity of $408,370.76. Finally, movements within the Cash and Banks account were reflected in the Cash Flow Statement.